The Role of the Banking Sector in Selected EEC Countries in the Context of a Changing Economic Environment - Agnieszka WOJCIK-MAZUR (Communications of International Proceedings, 2025)
The specificity of the financial system in European countries remains based mainly on the banking sector, which constitutes the primary source of capital for enterprises. Nevertheless, differences in the level of development of financial systems, including the banking sector, persist across Europe. Among the Central European countries, Poland, Romania, Slovenia, and Ukraine exhibit the lowest levels of development. It should be emphasized that, in the case of Ukraine—currently at war—a significant disparity between deposit levels and loan amounts is not an extraordinary phenomenon. In the case of Poland, however, it indicates an underutilized credit potential that could significantly contribute to investment growth and further economic development.
Keywords: Financial system; Banking sector; Central and Eastern Europe